Dropped Gallstones Causing a Perihepatic Abscess and Empyema - J. R. Robinson; J. K. Wright; S. K. Geevarghese (Case Reports in Surgery)
Iatrogenic perforation of the gallbladder during laparoscopic cholecystectomy is a well-known occurrence; however, the consequences of spillage of gallstones in the peritoneum and particularly intrathoracic complications are less defined. We describe the delayed development of a perihepatic abscess and empyema in a patient five years following laparoscopic cholecystectomy secondary to dropped gallstones. A 53-year-old man with medical history significant for a laparoscopic cholecystectomy five years prior to acute cholecystitis presented with purulent cough, hemoptysis, night sweats, and right-upper quadrant (RUQ) pain. Computed tomography (CT) scan revealed 5.4 cm right-sided subpulmonic and 5.9 cm perihepatic fluid collections with an 8 mm focal radiopaque density within the perihepatic fluid collection. Open intra-abdominal exploration resulted in retrieval of a 1 cm intraperitoneal gallstone. Laparoscopic cholecystectomy is a common surgical operation during which gallstone spillage can occur, causing both intra-abdominal and intrathoracic complications, presenting even years after surgery. This necessitates an attempt to retrieve all free intra-abdominal gallstones during the initial operation.